A kind of UV-resistant fluorine-free black photovoltaic backplane film and preparation method thereof
By adopting the black PET inner layer, support layer and outer layer structure in the photovoltaic backplane film, and adding hp-TiO2/PEA-GO composite material and light stabilizer to the outer layer, the problem of aging of traditional films under ultraviolet light is solved, and the effects of resistance to ultraviolet light and yellowing are achieved, extending service life and improving weather resistance.
Patent Information
- Application Number
- CN202411658361.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The traditional fluorine-containing PVDF film has short service life, is not environmentally friendly and has high cost. At the same time, the PET film will decolorize and degrade when exposed to ultraviolet light for a long time, resulting in a shorter service life.
The structure is adopted for the black PET inner layer, the black PET support layer and the black PET outer layer. The preparation materials of the black PET outer layer include hp-TiO2/PEA-GO composite material and light stabilizer, which are prepared by a spiral extrusion mechanism and formed by a three-layer coextrusion caster.
It achieves the effects of anti-ultraviolet rays and yellowing, improves the weather resistance and service life of the material, and avoids the use of fluorine, solving environmental protection and cost problems.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic cells, and in particular to an anti-ultraviolet fluorine-free black photovoltaic backplane film and a preparation method thereof. Background Art
[0002] Solar energy is the largest energy source among sustainable renewable energy sources. In order to fully utilize this energy source for the benefit of mankind, solar cells must be used to convert solar energy into photoelectricity. Solar cell backplane film is the material that encapsulates the back of solar cells. As a photovoltaic encapsulation material that directly contacts the external environment over a large area, it is required to have excellent aging resistance, insulation, water vapor barrier, weather resistance and other characteristics.
[0003] The traditional backplane film is a fluorinated PVDF film, which has problems such as short service life, environmental pollution and high cost. In order to solve the problems of short service life, high cost and environmental pollution of traditional PVDF film, PET film is usually used as a substitute. PET film has excellent optical properties, as well as excellent light transmittance, tensile strength and anti-aging properties. However, long-term exposure to ultraviolet rays will cause it to discolor and degrade. In order to avoid the aging of PET materials, it is necessary to develop a photovoltaic backplane film to improve the weather resistance of PET film and extend the service life of photovoltaic backplane film. Summary of the invention
[0004] The purpose of the present application is to provide a photovoltaic backplane film that is UV-resistant and yellowing-resistant.
[0005] To achieve the above objectives, the technical solution adopted in this application is: an anti-ultraviolet fluorine-free black photovoltaic backplane film, comprising a black PET inner layer, a black PET support layer and a black PET outer layer, and the raw materials for preparing the black PET outer layer include hp-TiO2 / PEA-GO composite material.
[0006] Preferably, the raw materials for preparing the black PET outer layer include black pigment, antioxidant, anti-hydrolysis agent, hp-TiO2 / PEA-GO composite material, light stabilizer, other additives and PET masterbatch.
[0007] As another preferred embodiment, the hp-TiO2 / PEA-GO composite material is prepared by: reacting nano-titanium oxide and terminal hydroxyl hyperbranched polyester to obtain hp-TiO2; reacting graphene oxide, polyetheramine and 4-dimethylaminopyridine to obtain PEA-GO powder; and reacting the hp-TiO2 and the PEA-GO to obtain the hp-TiO2 / PEA-GO composite material.
[0008] As another preferred embodiment, the light stabilizer is any one or more of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole, 2-(2ˊ-hydroxy-3ˊ5ˊ-di-tert-butylphenyl)-5-chloro-benzotriazole, 2,2'-methylene-(6-(2H-benzotriazole)-4-tert-octyl)phenol, 2-cyano-3,3ˊ-diphenylacrylate, sebacate bis-2,2,6,6-tetramethylpiperidinol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, and tris(2,4-di-tert-butylphenol) phosphite.
[0009] As another preferred embodiment, the light stabilizer is a mixture of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0010] As another preferred embodiment, the raw materials for preparing the black PET inner layer include black pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, other additives and PET masterbatch; the raw materials for preparing the black PET support layer include black pigment, modified pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, light stabilizer, other additives and PET masterbatch.
[0011] As another preferred embodiment, the raw materials for preparing the GMA acrylic copolymer include methyl methacrylate, glycidyl methacrylate, butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dibasic acid.
[0012] As another preference, the antioxidant is a combination of one or more of 2,4-dimethyl-6-tert-butylphenol, 1-hydroxy-3-methyl-4-isopropylbenzene, 2,2′-methylenebis(4-ethyl-6-tert-butylphenol), N,N′-di-2-naphthyl-p-phenylenediamine, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol.
[0013] A method for preparing an anti-ultraviolet fluorine-free black photovoltaic backplane film comprises the following preparation steps:
[0014] S1: reacting nano-titanium oxide with terminal hydroxyl hyperbranched polyester to obtain hp-TiO2; reacting graphene oxide, polyetheramine and 4-dimethylaminopyridine to obtain PEA-GO powder; reacting the hp-TiO2 with the PEA-GO to obtain a hp-TiO2 / PEA-GO composite material; S2: preparing a GMA acrylic copolymer from methyl methacrylate, glycidyl methacrylate, butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dibasic acid; S3: mixing a black pigment, an antioxidant, an anti-hydrolysis agent, the hp-TiO2 / PEA-GO composite material, a light stabilizer, other additives and a PET masterbatch; The method comprises the steps of: extruding the black pigment, the modified pigment, the antioxidant, the anti-hydrolysis agent, the GMA acrylic copolymer, the light stabilizer, the other additives and the PET masterbatch in a screw extruder to obtain a black PET support layer; extruding the black pigment, the antioxidant, the anti-hydrolysis agent, the GMA acrylic copolymer, the other additives and the PET masterbatch in a screw extruder to obtain a black PET inner layer; and molding the black PET inner layer, the black PET support layer and the black PET outer layer through a three-layer co-extrusion casting machine to obtain the UV-resistant fluorine-free black photovoltaic backplane film.
[0015] Further preferably, according to mass fraction, 1% to 10% of the black pigment, 0.1% to 2% of the antioxidant, 0.1% to 2% of the anti-hydrolysis agent, 0.1% to 2% of the hp-TiO2 / PEA-GO composite material, 0.1% to 2% of the light stabilizer, 0.5% to 2% of the other additives and the remainder of the PET masterbatch are extruded in a screw extruder to obtain the black PET outer layer.
[0016] Compared with the prior art, the beneficial effects of this application are:
[0017] (1) The present application adds hp-TiO2 / PEA-GO composite material to the UV-resistant fluorine-free black photovoltaic backplane film, which has a good UV-resistant effect and can absorb most of the ultraviolet rays to prevent them from penetrating the photovoltaic backplane film. In addition, the hp-TiO2 / PEA-GO composite material maintains stable chemical and physical properties under the irradiation of ultraviolet light and will not decompose or change color.
[0018] (2) In the UV-resistant fluorine-free black photovoltaic backplane film of the present application, the combination of hp-TiO2 / PEA-GO composite material and light stabilizer produces a good synergistic effect, further improving the weather resistance of the material, effectively blocking ultraviolet rays, reducing PET yellowing, and extending the service life of the PET film;
[0019] (3) The present application adds GMA acrylic copolymer to the black PET inner layer and the black PET support layer, and utilizes the epoxy functional groups of the GMA acrylic copolymer to chemically react with the carboxyl hydroxyl groups in PET. The two have strong compatibility, which promotes uniform dispersion of the system and plays a role in structural support. In addition, the GMA acrylic copolymer solves the problem of poor compatibility between the PET inner layer and the backplane substrate EVA, and effectively improves the polarity of the film and the interfacial bonding strength between the film and EVA. DETAILED DESCRIPTION
[0020] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0021] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0022] The present application provides an anti-ultraviolet fluorine-free black photovoltaic backplane film, comprising a black PET inner layer, a black PET support layer and a black PET outer layer, wherein the raw material for preparing the black PET outer layer comprises a hp-TiO2 / PEA-GO composite material.
[0023] In the present application, hp-TiO2 / PEA-GO composite material is added to the UV-resistant fluorine-free black photovoltaic backplane film as a UV absorber, which has good dispersibility in the PET material and is not easy to agglomerate. Visible light can pass through the PET film in large quantities, thereby making the photovoltaic backplane film have a higher transmittance at a wavelength of 380~1100 nm.
[0024] In addition, the hp-TiO2 / PEA-GO composite material has good anti-UV effect and can absorb most of the ultraviolet rays to prevent them from penetrating the photovoltaic backplane film. Under the irradiation of ultraviolet light, the hp-TiO2 / PEA-GO composite material maintains stable chemical and physical properties and will not decompose or discolor.
[0025] The hp-TiO2 / PEA-GO composite material is added to the PET film, has good compatibility with PET, and can cross-link with the polyester chain segments of PET, further improving the mechanical properties and stability of the PET photovoltaic backplane film.
[0026] The raw materials for preparing the black PET outer layer also include a light stabilizer, which can remain stable at high temperatures and protect the film material from damage by ultraviolet rays by capturing free radicals generated by ultraviolet light. In the anti-ultraviolet fluorine-free black photovoltaic backplane film of the present application, the combination of hp-TiO2 / PEA-GO composite material and light stabilizer produces a good synergistic effect, further improves the weather resistance of the material, effectively blocks ultraviolet rays, reduces PET yellowing, and extends the service life of the PET film.
[0027] The hp-TiO2 / PEA-GO composite material is prepared by the reaction of hp-TiO2 and PEA-GO, hp-TiO2 is hyperbranched polyester modified nano-titanium dioxide, and PEA-GO is polyetheramine grafted graphene oxide.
[0028] HP-TiO2 is obtained by reacting nano-titanium oxide and terminal hydroxyl hyperbranched polyester in a solvent, and removing impurities to obtain hyperbranched polyester modified nano-titanium dioxide, namely hp-TiO2. PEA-GO is obtained by reacting graphene oxide, polyetheramine and 4-dimethylaminopyridine, removing impurities and drying.
[0029] In some embodiments, the preparation steps of the hp-TiO2 / PEA-GO composite material are as follows: adding nano-titanium oxide and terminal hydroxyl hyperbranched polyester to a dimethylformamide solvent, heating the reaction and adding a certain amount of acetone, then filtering, washing and drying the product to obtain hp-TiO2; dispersing graphene oxide, polyetheramine and 4-dimethylaminopyridine in an N,N-dimethylformamide solution ice water bath, and dissolving the dehydrating agent N,N'-dicyclohexyldiimide in N,N-dimethylformamide, adding it dropwise to the ice water bath solution, removing N,N-dimethylformamide using a rotary evaporator, dialyzing the product completely in water, and obtaining PEA-GO powder after drying; adding hp-TiO2 to an ethanol solution of PEA-GO, filtering, washing and drying the product after the reaction is completed to obtain a hp-TiO2 / PEA-GO composite material.
[0030] The UV-resistant fluorine-free black photovoltaic backplane film of the present application comprises a black PET inner layer, a black PET support layer and a black PET outer layer, wherein the raw materials for preparing the black PET outer layer comprise black pigment, antioxidant, anti-hydrolysis agent, hp-TiO2 / PEA-GO composite material, light stabilizer, other additives and PET masterbatch.
[0031] In some embodiments, the raw materials for preparing the black PET inner layer include black pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, other additives and PET masterbatch.
[0032] In some embodiments, the raw materials for preparing the black PET support layer include black pigment, modified pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, light stabilizer, other additives and PET masterbatch.
[0033] The raw materials for preparing the GMA acrylic copolymer include: methyl methacrylate, glycidyl methacrylate (GMA), butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dibasic acid.
[0034] In some embodiments, the preparation method of GMA is as follows: methyl methacrylate, glycidyl methacrylate (GMA), butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dicarboxylic acid are placed in a reactor for reaction, extruded in a twin-screw extruder, and after devolatilization, a GMA acrylic copolymer is obtained.
[0035] In the present application, GMA acrylic copolymer is added to the black PET inner layer and the black PET support layer, and the epoxy functional group of the GMA acrylic copolymer is used to chemically react with the carboxyl hydroxyl group in PET. The two have strong compatibility, which promotes the uniform dispersion of the system and plays a role in structural support. In addition, the GMA acrylic copolymer solves the problem of poor compatibility between the PET inner layer and the backplane substrate EVA, and effectively improves the polarity of the film and the interface bonding strength between the film and EVA.
[0036] In some embodiments, the anti-hydrolysis agent is a combination of one or more of oxazoline compounds, epoxy compounds, aromatic carbodiimide, aliphatic carbodiimide, and polycarbodiimide.
[0037] More preferably, the anti-hydrolysis agent is a mixture of monomeric carbodiimide PZ-3000 and homopolymeric carbodiimide UN-025 anti-hydrolysis agent.
[0038] The present application uses a combination of monomeric carbodiimide PZ-3000 and homopolymeric carbodiimide UN-025 anti-hydrolysis agent as a high-efficiency anti-hydrolysis agent. The monomeric carbodiimide has little effect on the color of the PET material and effectively inhibits the hydrolysis reaction of the PET material. The homopolymeric carbodiimide makes the PET material have high viscosity and mechanical strength. The coordinated effect of the two greatly improves the hydrolysis resistance of the PET material while having certain oxidation resistance and high temperature resistance, greatly improving the weather resistance and aging resistance of the backplane film, thereby ensuring a high reflectivity of the photovoltaic backplane to sunlight and extending the service life.
[0039] In some embodiments, the antioxidant is a combination of one or more of 2,4-dimethyl-6-tert-butylphenol, 1-hydroxy-3-methyl-4-isopropylbenzene, 2,2′-methylenebis(4-ethyl-6-tert-butylphenol), N,N′-di-2-naphthyl-p-phenylenediamine, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol.
[0040] More preferably, the antioxidant is a mixture of 1-hydroxy-3-methyl-4-isopropylbenzene and 2,6-di-tert-butyl-α-dimethylamino-p-cresol, which are mixed in a mass ratio of (2-4): (0.5-2).
[0041] Since photovoltaic backplane films will discolor and degrade when exposed to ultraviolet rays for a long time, traditional PET materials will have chain breaking problems when oxidized. The carboxyl groups generated by chain breaking will further catalyze the cracking of PET polyester, thereby accelerating the aging of the film. This application uses 1-hydroxy-3-methyl-4-isopropylbenzene and 2,6-di-tert-butyl-α-dimethylamino-p-cresol as antioxidants to significantly reduce yellowing and aging; at the same time, it synergizes with titanium dioxide to avoid chain breakage caused by aggregation of material molecular chains and enhance the stability of the system.
[0042] In some embodiments, the light stabilizer is any one or more of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole, 2-(2ˊ-hydroxy-3ˊ5ˊ-di-tert-butylphenyl)-5-chloro-benzotriazole, 2,2'-methylene-(6-(2H-benzotriazole)-4-tert-octyl)phenol, 2-cyano-3,3ˊ-diphenylacrylate, sebacate bis(2,2,6,6-tetramethylpiperidinol), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, and tris(2,4-di-tert-butylphenol) phosphite.
[0043] More preferably, the light stabilizer is a mixture of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0044] The present application uses bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole in combination as light stabilizers, which can significantly improve the weather resistance of the backplane film and prevent it from losing gloss, cracking, bubbling, falling off and discoloration.
[0045] In some embodiments, the modified pigment is any one or more of titanium dioxide, calcium carbonate, montmorillonite, kaolin, barium sulfate, titanium dioxide, silicon dioxide and aluminum oxide.
[0046] More preferably, the modified pigment is a mixture of titanium dioxide and organo-montmorillonite.
[0047] The present application adds modified pigments to the black PET support layer. Titanium dioxide has the advantages of stable chemical properties, high toughness, oxidation resistance, high temperature resistance, antibacterial properties and high reflectivity, which enhances the weather resistance of the PET film. Organic montmorillonite can act as a nucleating agent, making PET less likely to break, and effectively improving the comprehensive mechanical properties of the PET film. In addition, organic montmorillonite has good barrier properties, making PET materials less likely to be thermally decomposed; organic montmorillonite combines with PET through ionic bonds, inhibiting the influence of local discharge on the PET system, improving the electrical properties of the PET film, and enhancing the aging resistance and insulation of the PET substrate.
[0048] In some embodiments, the other auxiliary agent includes a combination of one or more of a curing agent, a dispersant, or a plasticizer.
[0049] The photovoltaic backplane film of the present application uses PET as the material of the multi-layer base film. PET has excellent optical properties, and excellent insulation performance, tensile strength and anti-aging performance. It does not contain fluorine elements and is environmentally friendly. It solves the problems of traditional fluorinated PVDF films such as short service life, environmental pollution and high cost.
[0050] The present application provides a method for preparing an ultraviolet-resistant fluorine-free black photovoltaic backsheet, comprising the following steps:
[0051] S1: Add nano-titanium oxide and terminal hydroxyl hyperbranched polyester to dimethylformamide solvent, heat the reaction and add a certain amount of acetone, then filter, wash and dry the product to obtain hp-TiO2; disperse graphene oxide, polyetheramine and 4-dimethylaminopyridine in an N,N-dimethylformamide solution ice-water bath, dissolve the dehydrating agent N,N'-dicyclohexyldiimide in N,N-dimethylformamide, add dropwise to the ice-water bath solution, remove N,N-dimethylformamide by rotary evaporator, dialyze the product completely in water, and obtain PEA-GO powder after drying; add hp-TiO2 to an ethanol solution of PEA-GO, filter, wash and dry the product after the reaction is completed to obtain a hp-TiO2 / PEA-GO composite material;
[0052] S2: placing methyl methacrylate, glycidyl methacrylate (GMA), butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dicarboxylic acid into a reactor for reaction, extruding in a twin-screw extruder, and obtaining a GMA acrylic copolymer after devolatilization;
[0053] S3: extruding black pigment, antioxidant, anti-hydrolysis agent, hp-TiO2 / PEA-GO composite material, light stabilizer, other additives and PET masterbatch in a screw extruder to prepare a black PET outer layer;
[0054] The black pigment, the modified pigment, the antioxidant, the anti-hydrolysis agent, the GMA acrylic copolymer, the light stabilizer, other additives and the PET masterbatch are extruded in a screw extruder to prepare a black PET support layer;
[0055] The black pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, other additives and PET masterbatch are extruded in a screw extruder to prepare a black PET inner layer;
[0056] The black PET inner layer, the black PET support layer and the black PET outer layer are formed by a three-layer co-extrusion casting machine to obtain an anti-ultraviolet fluorine-free black photovoltaic backplane film of the present application.
[0057] The preparation process of the UV-resistant fluorine-free black photovoltaic backplane film of the present application is simple. The prepared black fluorine-free photovoltaic backplane film has good adhesion, mechanical properties, hydrolysis resistance, UV resistance and weather resistance. It is beautiful and can significantly improve the service life of the photovoltaic backplane.
[0058] In some embodiments, 1% to 10% black pigment, 0.1% to 2% antioxidant, 0.1% to 2% anti-hydrolysis agent, 0.1% to 2% hp-TiO2 / PEA-GO composite material, 0.1% to 2% light stabilizer, 0.5% to 2% other additives and the remainder of PET masterbatch are extruded in a screw extruder according to mass fraction to obtain a black PET outer layer.
[0059] In some embodiments, 1% to 10% black pigment, 2% to 10% modified pigment, 0.1% to 2% antioxidant, 0.1% to 2% anti-hydrolysis agent, 10% to 20% GMA acrylic copolymer, 0.1% to 2% light stabilizer, 0.5% to 2% other additives and the remainder PET masterbatch are extruded in a screw extruder according to mass fraction to prepare a black PET support layer.
[0060] In some embodiments, 1% to 10% black pigment, 0.1% to 2% antioxidant, 0.1% to 2% anti-hydrolysis agent, 10% to 20% GMA acrylic copolymer, 0.5% to 2% other additives and the remainder of PET masterbatch are extruded in a screw extruder according to mass fraction to prepare a black PET inner layer.
[0061] Example 1
[0062] S1: 5 g of nano-titanium oxide and 100 g of terminal hydroxyl hyperbranched polyester were added to 500 g of dimethylformamide solvent, heated to 60 °C, ultrasonically mixed for 40 min, then heated to 120 °C, stirred for 24 h, then added 2 L of acetone, stirred evenly to obtain a mixed solution, vacuum filtered the mixed solution, repeatedly washed with anhydrous ethanol to remove unreacted terminal hydroxyl hyperbranched polyester and excess solvent, and finally vacuum dried at 60 °C for 6 h to obtain hp-TiO2;
[0063] 5 g of graphene oxide, 50 g of polyetheramine and 3 g of 4-dimethylaminopyridine were dispersed in 200 g of N, N-dimethylformamide and ultrasonicated for 5 min, and then placed in an ice bath for cooling for 25 min to obtain a mixed solution; secondly, 20 g of dehydrating agent N, N'-dicyclohexyl diimide was dissolved in 100 g of N, N-dimethylformamide and added dropwise to the above mixed solution; then the ice bath was removed, and the reaction was stirred at 30 ° C for 12 h, and N, N-dimethylformamide was removed by a rotary evaporator. The product was completely dialyzed in water, and finally vacuum dried at 65 ° C for 4 h to obtain PEA-GO powder;
[0064] 20g of PEA-GO powder was dispersed in ethanol water and ultrasonicated for 8 min to obtain a 20% PEA-GO dispersion. The hp-TiO2 powder was added to the PEA-GO dispersion and stirred at 80 °C for 4 h. The dispersion was transferred to a reactor and reacted at 165 °C for 12 h. After cooling to room temperature, the supernatant was removed by centrifugation. After repeated washing, the dispersion was vacuum dried at 65 °C for 8 h to obtain the hp-TiO2 / PEA-GO composite material.
[0065] S2: 92% methyl methacrylate, 5% glycidyl methacrylate (GMA), 2% butyl acrylate, 0.7% styrene, 0.1% benzoyl peroxide, 0.1% azobisisobutyronitrile, and 0.1% dodecyl dibasic acid were added into a polymerization reactor, and free radical polymerization was carried out at 150°C for 18 h. The melt was fed into a twin-screw extruder through a gear pump, and the extrusion temperature was 190°C. After atmospheric pressure devolatilization and vacuum devolatilization, a GMA acrylic functional copolymer was obtained;
[0066] S3: 5% carbon black, 10% GMA acrylic copolymer, 0.7% antioxidant, 1% anti-hydrolysis agent, 1% additive and the balance PET masterbatch are mixed evenly in a high-speed mixer, and the mixed raw materials are added to a screw extruder, and extruded and melted at a temperature of 220°C and a screw speed of 15 r / min to obtain a black PET inner layer;
[0067] 5% carbon black, 10% GMA acrylic copolymer, 5% modified pigment, 0.7% antioxidant, 1% anti-hydrolysis agent, 1% light stabilizer, 1% additive and the rest PET masterbatch were mixed evenly in a high-speed mixer, and the mixed raw materials were added into a screw extruder, and extruded and melted at a temperature of 220°C and a screw speed of 20 r / min to obtain a black PET support layer;
[0068] 5% carbon black, 0.7% antioxidant, 1% anti-hydrolysis agent, 1.2% hp-TiO2 / PEA-GO composite material, 1% light stabilizer, 1% additive and the rest of PET masterbatch were mixed evenly in a high-speed mixer, and the mixed raw materials were added into a screw extruder, and extruded and melted at a temperature of 220 ° C and a screw speed of 15 r / min to obtain a black PET outer layer;
[0069] The black PET inner layer, the black PET support layer and the black PET outer layer are formed by a three-layer co-extrusion casting machine to obtain an anti-ultraviolet fluorine-free black photovoltaic backplane film of the present application.
[0070] Among them, the anti-hydrolysis agent is a mixture of 70% monomeric carbodiimide PZ-3000 and 30% homopolymeric carbodiimide UN-025; the antioxidant is a mixture of 50% 1-hydroxy-3-methyl-4-isopropylbenzene and 50% 2,6-di-tert-butyl-α-dimethylamino-p-cresol; the modified pigment is a mixture of 60% titanium dioxide and 40% organic montmorillonite; the light stabilizer is a mixture of 50% bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate and 50% 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole.
[0071] Example 2
[0072] The addition amount of hp-TiO2 / PEA-GO composite material was adjusted to 0.6%, and the other preparation steps were consistent with the preparation steps in Example 1.
[0073] Example 3
[0074] The addition amount of hp-TiO2 / PEA-GO composite material was adjusted to 1%, and the other preparation steps were consistent with the preparation steps in Example 1.
[0075] Comparative Example 1
[0076] No light stabilizer was added to the black PET outer layer, and the other preparation steps were consistent with those in Example 1.
[0077] Comparative Example 2
[0078] No hp-TiO2 / PEA-GO composite material was added to the black PET outer layer, and the other preparation steps were consistent with the preparation steps in Example 1.
[0079] Performance Testing
[0080] The photovoltaic backsheet films of Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to adhesive adhesion tests according to the ASTM D3359-09 tape method; the chromaticity values b were tested according to the HGT 3862-2006 yellow index test method; and the test samples were subjected to UV aging test at 120 KWh / m 2 The yellowing index value △b, wherein the closer the chromaticity value b is to 0, the darker the color, and the closer the yellowing index value △b is to 0, the better the color consistency. The performance test results are recorded in the following Table 1.
[0081] Table 1 Performance test results of various embodiments and comparative examples
[0082]
[0083] Analyzing the performance test results of the embodiments, the UV-resistant fluorine-free black photovoltaic backsheet of the present application can achieve good color consistency, low yellowing index and good adhesion with the EVA adhesive layer, and can be used as a photovoltaic backsheet film to significantly extend the service life of photovoltaic modules.
[0084] Analysis of the performance test results of Example 1, Comparative Example 1 and Comparative Example 2 shows that the hp-TiO2 / PEA-GO composite material and the light stabilizer do not affect the bonding strength between the photovoltaic backplane film and EVA. The combined use of the hp-TiO2 / PEA-GO composite material and the light stabilizer can significantly reduce the chromaticity value and yellowing index of the photovoltaic backplane film, improve the yellowing problem of PET, and extend the service life of the photovoltaic backplane film.
[0085] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. An anti-ultraviolet fluorine-free black photovoltaic backplane film, characterized in that: The invention comprises a black PET inner layer, a black PET supporting layer and a black PET outer layer, wherein the raw material for preparing the black PET outer layer comprises a hp-TiO2 / PEA-GO composite material, and the preparation method of the hp-TiO2 / PEA-GO composite material is as follows: reacting nano titanium oxide with terminal hydroxyl hyperbranched polyester to obtain hp-TiO2; reacting graphene oxide, polyetheramine and 4-dimethylaminopyridine to obtain PEA-GO powder; reacting the hp-TiO2 with the PEA-GO to obtain the hp-TiO2 / PEA-GO composite material; The raw materials for preparing the black PET outer layer include black pigment, antioxidant, anti-hydrolysis agent, hp-TiO2 / PEA-GO composite material, light stabilizer, other additives and PET masterbatch; the raw materials for preparing the black PET inner layer include black pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, other additives and PET masterbatch; the raw materials for preparing the black PET support layer include black pigment, modified pigment, antioxidant, anti-hydrolysis agent, GMA acrylic copolymer, light stabilizer, other additives and PET masterbatch; the raw materials for preparing the GMA acrylic copolymer include methyl methacrylate, glycidyl methacrylate, butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dibasic acid; the other additives include a combination of one or more of a curing agent, a dispersant or a plasticizer.
2. The UV-resistant fluorine-free black photovoltaic backsheet film according to claim 1, characterized in that: The light stabilizer is any one or more of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole, 2-(2ˊ-hydroxy-3ˊ5ˊ-di-tert-butylphenyl)-5-chloro-benzotriazole, 2,2'-methylene-(6-(2H-benzotriazole)-4-tert-octyl)phenol, 2-cyano-3,3ˊ-diphenylacrylate, sebacate bis(2,2,6,6-tetramethylpiperidinol), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, and tris(2,4-di-tert-butylphenol) phosphite.
3. The UV-resistant fluorine-free black photovoltaic backsheet film according to claim 2, characterized in that: The light stabilizer is a mixture of bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) sebacate and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
4. The UV-resistant fluorine-free black photovoltaic backsheet film according to claim 1, characterized in that: The antioxidant is a combination of one or more of 2,4-dimethyl-6-tert-butylphenol, 1-hydroxy-3-methyl-4-isopropylbenzene, 2,2′-methylenebis(4-ethyl-6-tert-butylphenol), N,N′-di-2-naphthyl-p-phenylenediamine, and 2,6-di-tert-butyl-α-dimethylamino-p-cresol.
5. A method for preparing an anti-ultraviolet fluorine-free black photovoltaic backplane film, characterized in that: The method comprises the following preparation steps: S1: reacting nano-titanium oxide and terminal hydroxyl hyperbranched polyester to obtain hp-TiO2; reacting graphene oxide, polyetheramine and 4-dimethylaminopyridine to obtain PEA-GO powder; reacting the hp-TiO2 and the PEA-GO to obtain a hp-TiO2 / PEA-GO composite material; S2: GMA acrylic copolymer prepared from methyl methacrylate, glycidyl methacrylate, butyl acrylate, styrene, benzoyl peroxide, azobisisobutyronitrile and dodecyl dibasic acid; S3: extruding a black pigment, an antioxidant, an anti-hydrolysis agent, the hp-TiO2 / PEA-GO composite material, a light stabilizer, other additives and a PET masterbatch in a screw extruder to obtain a black PET outer layer, wherein the other additives include a curing agent, a dispersant or a combination of one or more of a plasticizer; Extruding a black pigment, a modified pigment, an antioxidant, an anti-hydrolysis agent, the GMA acrylic copolymer, a light stabilizer, other additives and a PET masterbatch in a screw extruder to prepare a black PET support layer, wherein the other additives include a combination of one or more of a curing agent, a dispersant or a plasticizer; Extruding a black pigment, an antioxidant, an anti-hydrolysis agent, the GMA acrylic copolymer, other additives and PET masterbatch in a screw extruder to prepare a black PET inner layer, wherein the other additives include a combination of one or more of a curing agent, a dispersant or a plasticizer; The black PET inner layer, the black PET support layer and the black PET outer layer are formed by a three-layer co-extrusion casting machine to obtain the UV-resistant fluorine-free black photovoltaic backplane film.
6. The method for preparing the UV-resistant fluorine-free black photovoltaic backplane film according to claim 5, characterized in that: According to mass fraction, 1% to 10% of the black pigment, 0.1% to 2% of the antioxidant, 0.1% to 2% of the anti-hydrolysis agent, 0.1% to 2% of the hp-TiO2 / PEA-GO composite material, 0.1% to 2% of the light stabilizer, 0.5% to 2% of the other additives and the balance of the PET masterbatch are extruded in a screw extruder to obtain the black PET outer layer.
Citation Information
Patent Citations
Monofunctional polyether amine modified oxidized graphene / epoxy resin nanometer composite material with high strength and high tenacity
CN109467886A
PVDF composite film for solar cell backboard and preparation method of PVDF composite film
CN109950350A
Uvioresistant extinction cation polyester fiber
CN116837486A
High-reflectivity strengthened black backboard film, preparation method and application thereof
CN118636553A